2019
DOI: 10.1038/s41514-019-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan-increasing drug nordihydroguaiaretic acid inhibits p300 and activates autophagy

Abstract: Aging is characterized by the progressive loss of physiological function in all organisms. Remarkably, the aging process can be modulated by environmental modifications, including diet and small molecules. The natural compound nordihydroguaiaretic acid (NDGA) robustly increases lifespan in flies and mice, but its mechanism of action remains unclear. Here, we report that NDGA is an inhibitor of the epigenetic regulator p300. We find that NDGA inhibits p300 acetyltransferase activity in vitro and suppresses acet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Aspirin induces autophagy through the inhibition of EP300 14 16 . However, inhibition of EP300 with its pharmacological antagonist C646 is not sufficient to induce protein deacetylation in cultured cells, contrasting with salicylate that significantly reduces acetylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspirin induces autophagy through the inhibition of EP300 14 16 . However, inhibition of EP300 with its pharmacological antagonist C646 is not sufficient to induce protein deacetylation in cultured cells, contrasting with salicylate that significantly reduces acetylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These include cyclooxygenases 1 and 2 (responsible for the generation of proinflammatory and platelet-aggregating prostaglandins and thromboxanes) 10 , but also a series of other proteins including the energy sensor AMP-activated protein kinase (AMPK) 11 and the proinflammatory NF-kB (nuclear factor kappa-light-chain-enhancer of activated B cells) activating kinase IKKβ (inhibitor of nuclear factor kappa-B kinase subunit beta) 12 , 13 . Recently, we and others have shown that salicylate can also inhibit the acetyltransferase activity of E1A-associated protein p300 (EP300) 14 16 . By inhibiting EP300, aspirin stimulates autophagy, a cytoplasmic renewal process that has prominent cardioprotective and antineoplastic effects 17 20 , perhaps explaining the long-term effects of aspirin on the two major age-related disease categories, namely, cardiovascular disease and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Examples for this category of "senomorphics" (or alternatively, "senostatics") include but are not limited to apigenin, kaempferol, glucosamine, 4,4′-dimethoxychalcone, nordihydroguaiaretic acid and resveratrol. [94][95][96][97][98][99] To date, there are two different types of "senomorphics," including one that controls the SASP regulatory network and the other specifically against a certain component of the SASP. For the former, a group of therapeutic targets have already emerged as key nodes of the SASP signaling network and were mechanistically dissected, including but not limited to NF-B, p38MAPK, GATA4, mTOR, BRD4, and TAK1, thus providing optimal targets to develop effective solutions.…”
Section: Senomorphics or Senostaticsmentioning
confidence: 99%
“…Sirtuins [ 156] Piperlongumine Natural (piper plants) Caspase 3 [58] FOXO4-DRI peptide Synthetic FOXO4-p53 interaction [48] Alvespimycin (17-DMAG) Synthetic (geldanamycin derivative) HSP90 [47] Senomorphics Apigenin Natural (plants, fruits, vegetables, tea) NF-B [94] Kaempferol Natural (fruits, vegetables) NF-B [94] Glucosamine Natural (Dietary supplements) ROS, p21 CIP1 , autophagy [ 157,158] Nordihydroguaiaretic acid (NDGA) Natural (Creosote bush) p300 acetyltransferase [97] Resveratrol Natural (fruits, red wine, dietary supplements) SIRT1 [ 159,160] Rapamycin S. hygroscopicus mTOR [ 103,104] Metformin Synthetic AMPK [ 161,162] Ruxolitinib Synthetic JAK1/2 [ 163] SB203580 Synthetic p38MARPK [ 101] 5Z-7-oxozeaenol Synthetic TAK1 [ 106] or more accurately, personalized. In response to the urgent and unmet clinical, healthcare, workforce, and economic needs of global aging populations who are suffering from aging-related conditions and multimorbidity, the world health organization (WHO) has recently called for a public health attention based on the law of human rights.…”
Section: Ubx0101mentioning
confidence: 99%
“…Second, acetylation of several proteins by p300 and/or CBP have been shown to be involved to be involved in agingrelated processes, including WRN, C/EBPα and TAU [26][27][28][29]. Third, lifespan extension in model organisms, through either dietary/caloric restriction or pharmacological mimetics of dietary restriction, requires CBP and p300 [30][31][32][33][34][35][36]. Finally, studies in C. elegans have directly demonstrated that reduced expression of CBP or p300 shortens lifespan [37][38][39][40].…”
Section: Cbp/p300mentioning
confidence: 99%